Managing with humour during COVID 19: Managers’ humour style and its influence on team members’ stress and job satisfaction using non-hierarchical cluster analysis - Kairanna, Sneha S; Annamalai, Sumathi; Gada, Jagrat (The journal of contemporary issues in business and government, 2022)
This research paper focuses on exploring the usage of humour by the managers while connecting with their teams. The objective is to study which humour style is effective in reducing the stress level and increasing the job satisfaction level of the team members using K- means cluster analysis. 120 team members evaluated their manager’s humour. K- means cluster analysis reported specific humour clusters. The results confirm that affiliative humour and self-enhancing humour decreases the stress level of the team members and increases the job satisfaction. The findings suggest that managers who apply self-defeating and aggressive humour are most likely to damage the manager and team member’s relationship. It is also observed that usage of negative humour is most likely to be causing strain than not using humour at all, while interacting. This study helps managers to identify the most effective humour styles to be adopted, while engaging with their teams.